Observational Study on the Efficacy of Azadirachta indica 30C in Atopic Respiratory Disorders: Assessment of Serum Immunoglobulin E Levels” (Homoeopathy for All, 2025)
Background: Atopic disorders are  a significant global health issue,  affecting 5%–30% of the population.  Type I hypersensitivity reactions,  mediated byz immunoglobulin E  (IgE), play a central role in atopic  respiratory complaints. This study  evaluates the effect of Azadirachta  indica 30C in reducing serum IgE  levels. ¹⁻³ Objective: To assess the variation of  serum IgE levels before, during, and  after intervention with Azadirachta  indica 30C in patients with atopic  respiratory complaints. Materials and Methods: Thirty  cases of atopic respiratory complaints  (diagnosed based on clinical history,  CMDT guidelines, and initial serum  IgE levels) were selected using  purposive sampling. Azadirachta  indica 30C was administered twice  daily for 2 weeks, with placebos  given in between, and patients were  followed for 3 months. Serum IgE  levels were measured monthly. Data  were analyzed using mean, standard  deviation, and repeated measures  ANOVA. Results: ANOVA showed a highly  significant reduction in serum  IgE levels (P = 0.000). Pairwise  comparisons demonstrated  significant decreases between pre and during-treatment (P = 0.007)  and during- and post-treatment (P =  0.016) measurements. Conclusion: Homoeopathic  treatment with Azadirachta indica  30C leads to a significant reduction  in serum IgE levels in patients with  atopic respiratory complaints.
Keywords: Atopic respiratory disorders; Azadirachta indica 30C; Immunoglobulin E; Homoeopathy; Observational study